TRANSFORMASI GAYA BAHASA DALAM KARYA SASTRA TERJEMAHAN - Siti Hariti Sastriyani (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
In the francophone literature entitled Le Rocher de Tanios, (which is translated into “Cadas Tanios” in Indonesian), there are numerous transformations of the styles. When compared with Cadas Tanios, the styles in Le Rocher de Tanios exhibit several forms of transformations. Those forms may be recognized as the different style and the zero style once the French text has been translated into the Indonesian text. It can also be said that the “x” style in the French text creates a “y” style in the Indonesian text. The x style in the French text may also create the zero style in the Indonesian text. In addition, the zero style in the French text may create the Indonesian “x” or “y” style. However, the other form of Indonesian style in Cadas Tanios has the same style as that in the French style. The transformations of the styles in Cadas Tanios indicate that there are creations and innovations in the translation literature, and in the future the translations of the French literature into Indonesian literature may well benefit from this analysis.